2020
DOI: 10.1002/ca.23670
|View full text |Cite
|
Sign up to set email alerts
|

Effective botulinum neurotoxin injection in treating iliopsoas spasticity

Abstract: Introduction To detect ideal locations for botulinum toxin (BoNT) injection by exploring the intramuscular nerve arborization of the psoas major and iliacus muscles. Method A modified Sihler's method was performed on the psoas major and iliacus muscles (16 specimens each). Intramuscular nerve arborization was recorded according to the most prominent point of the anterior superior iliac spine (ASIS), the posterior superior iliac spine (PSIS), the lesser trochanter (LT), and the transverse process of the 12th th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…Consequently, to enhance the effectiveness and mitigate the negative effects of BoNT injection, it needs to be made directly into the neural arborized areas. To determine the injection spot for BoNT, studies have concentrated on finding the neural arborized areas within the muscles 17–22. Additionally, previous studies have reported neurological damage resulting from mechanical injury when injection treatments have been performed at the nerve trunk, in the place where the nerve punctures into muscle tissue 23…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to enhance the effectiveness and mitigate the negative effects of BoNT injection, it needs to be made directly into the neural arborized areas. To determine the injection spot for BoNT, studies have concentrated on finding the neural arborized areas within the muscles 17–22. Additionally, previous studies have reported neurological damage resulting from mechanical injury when injection treatments have been performed at the nerve trunk, in the place where the nerve punctures into muscle tissue 23…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to lessen the undesirable effects and enhance efficiency, LD muscle BoNT injection should be targeted into the neural arborized zones. Studies have focused primarily on identifying the intramuscular arborized zones and guidance injectable points for BoNT treatments [35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that explain BoNT injection locations by navigating intramuscular neural distribution with naked eye dissection have limits, such as perceiving minuscule nerves and the likelihood of neural damage [17,21,25,[41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%